Learning to Teach Multicultural Science: What Do New Teachers Bring?. Issue 3 (2nd July 2020) - Kye, Hannah
ABSTRACT: While important theoretical work has helped define the goals of teacher professional development in multicultural science education (MSE), less is known about how beginning elementary teachers' strengths may inform this work. The purpose of this case study is to examine potential starting points for professional development based on elementary teachers' beliefs and practices regarding MSE. Three beginning science teachers participated in the study. Qualitative data were collected through individual interviews, classroom observations, and focus group interviews. The teachers' beliefs and practices regarding MSE were analyzed inductively and deductively. Constant comparative analysis revealed three common starting points, described thematically in the findings as situating science in social issues, understanding of science teaching as relational work, and critically examining traditional school science. These dispositions and knowledge regarding MSE inform recommendations for more effective professional development opportunities. Implications for future research are discussed.